REACH Story of Change: building drought resilience in Ethiopian river basins - REACH (University of Oxford, 2024)
REACH Ethiopia partner WLRC are implementing, with the Ministry of Water and Energy (MoWE), Ethiopia, a €45 million programme, BRIGHT, to improve resilience and reduce vulnerability to drought and climate change in Ethiopia, working in five river basins. BRIGHT will build upon and scale up WLRC research on water resources management, climate science, water quality and inequalities to benefit an estimated 2.5 million people directly, and over 50 million people indirectly. REACH has supported WLRC to build their capacity and leadership in water security in Ethiopia, with a rich track record in publishing and a strong team on climate resilience, groundwater, water quality and inequalities in the Awash basin. Structured engagement with MoWE and officers working in the Awash Basin through demand-led science and capacity building has created strong partnerships between WLRC and the government. This Story of Change reflects on the partnerships and processes that have facilitated this success for WLRC and for Ethiopia, and in particular on three areas: building their leadership in water security science; building trusted relationships with practitioner partners; and training the next generation of water security leaders.